The Meaning of Dukhan and Wardatan Ka-ddihan in Surah Ad-Dukhan (10-11) and Surah Ar-Rahman (37): A Scientific Thematic Study - Habibullah, Ilham; Anggara, Deki Ridho Adi; Rifaannudin, Mahmud; Pratiwi, Utari Nur (QiST: Journal of Quran and Tafseer Studies, 2025)
This study examines the Quranic terms "Dukhān" and "Wardatan Ka-ddihān" found in Surah Ad-Dukhan (10–11) and Surah Ar-Rahman (37) through a thematic scientific lens. Using a qualitative approach, it bridges classical tafsir (interpretation) with modern astronomical insights. The term "Dukhān" is interpreted as cosmic dust, possibly symbolizing the universe's final phase, while "Wardatan Ka-ddihān" is linked to the explosive death of a star, resembling nebulae such as the Rosette Nebula. These findings suggest that the Quran contains descriptions that align with observable cosmic phenomena, highlighting its relevance to scientific exploration. The research underscores the potential of religious texts to inspire inquiry and deepen understanding of the universe. By integrating faith and science, this study encourages interdisciplinary dialogue and opens new pathways for interpreting sacred texts in light of contemporary knowledge. Ultimately, it contributes to both Quranic scholarship and the broader conversation on the harmony between spirituality and scientific discovery.